Tangent spaces to metric spaces and to their subspaces - Dovgoshey, O.A. (Інститут прикладної математики і механіки НАН України, 2008)
We investigate tangent spaces and metric space valued derivatives at points of a general metric spaces. The conditions under which two different subspaces of the metric space have isometric tangent spaces in the common point of these subspaces are determinated.